Monitoreo de las plantas de secado - Bode, P. (International Center for Tropical Agriculture, 1988)
A method used to calculate a social impact indicator of the cassava drying project carried out on Colombia`s Atlantic Coast is described. Based on the information collected during project monitoring (amount of cassava sold, sale price, labor costs, profits, no. of beneficiaries and land tenancy, and investment costs), the impact of the project from Aug. 1987 through July 1988 is also analyzed. Income generated by the project, both directly (through cassava processing) and indirectly (increased vol. of cassava produced by farmer), is considered the major factor determining social impact. Adequate distribution of this income in benefit of the poorer sectors is also considered important. Three parameters are proposed to express social impact: (1) an absolute social impact, which is the relationship between the total benefits generated by the project and investment costs; (2) a relative social impact, which indicates the no. of beneficiaries of the project relative to the distribution of benefits towards the poorer sectors of the population; and (3) a social impact indicator, which combines the former parameters and allows plant classification according to the impact obtained. (CIAT)